Aquatic Exercise for Treatment of Low-Back Pain: A Systematic Review of Randomized Controlled Trials. (March 2013) - Olson, Daniel A.; Kolber, Morey J.; Patel, Chetan; Pabian, Patrick; Hanney, William J.
Low-back pain (LBP) is a medical condition that affects most people at some point in their lives. Exercise therapy has been found to be efficacious in treating LBP in some individuals; however, it is unclear which form of exercise demonstrates superior outcomes. It has been postulated that exercise combined with the unique properties of water may demonstrate favorable outcomes. Moreover, studies have evaluated the effectiveness of aquatic therapy as an intervention for patients with LBP. This review aims to explore the efficacy of aquatic therapy as an intervention for LBP. The findings from this review suggest that aquatic therapy is superior to no treatment; however, it did not always prove more effective when compared with other forms of conservative treatment. Whereas the outcome of this review supports aquatic therapy as an effective treatment for LBP, further research is needed to determine if it is superior to other interventions.